Influence of vibration on the grain flow sensor during the harvest and the difference elimination method - Qian, Pengfei; Lu, Ting; Shen, Cheng; Chen, Shuren (International Journal of Agricultural and Biological Engineering, 2021)
The grain yield data collected by the intelligent yield measurement system of the combine harvester is generated into a field plot yield distribution map, which is great significance for guiding agricultural production. However, in the process of drawing the yield map, the combine harvester is affected by vibration during operation and the generated error data in the process of collecting data which will cause the drawing results to be inaccurate. This study researched two factors that cause errors, then, the influence of vibration interference on the measurement signal was eliminated by filtering, vibration isolation, and designing a double-plates differential grain flow sensor. Three methods were taken to eliminate random errors, gross errors and systematic errors, including using the arithmetic average value to replace the true value, the 3σ criterion, and removing the filling time data and the delaying time data. Finally, the grain yield distribution map was obtained through Matlab and Excel. The results showed that the interference frequency above 50 Hz could be eliminated by filtering, but it was difficult to filter the low frequency signal which was close to the grain impact frequency. The vibration amplitude was reduced to 14.29% by adding vibration isolation plate, and the SNR was increased from −4.67 dB to 29.21 dB by combining low-pass filtering and damping vibration isolation. When the grain feeding rate was 2 kg/s, the natural vibration amplitude of the sensor after difference was about 0.02 V and evenly distributed around the zero voltage 0.2 V. The influence of positive and negative offset on the average value of grain impact signal could be ignored, and the signal-to-noise ratio was increased from 29.21 dB to 62.49 dB. The results of field experiments showed that the yield map drawn can clearly display the yield value of the harvest area, which is used to guide agricultural production. Keywords: combine harvester, grain flow sensor, vibration interference, double-plates differential, elimination method DOI: 10.25165/j.ijabe.20211405.6748 Citation: Qian P F, Lu T, Shen C, Chen S R. Influence of vibration on the grain flow sensor during the harvest and the difference elimination method. Int J Agric & Biol Eng, 2021; 14(5): 149–162.